Cardiomyocyte changes in the metabolic syndrome and implications for endogeneous protective strategies. (March 2014) - Oosterlinck, Wouter; Herijgers, Paul
<x xml:space="preserve">Abstract</x> The deadly quartet of the metabolic syndrome includes obesity, impaired glucose tolerance, an atherogenic lipid profile and hypertension. The synergistic effects of these comorbidities lead to a combination of functional and structural cardiomyocyte changes and finally result in a global adverse remodeling process. Overall cardiovascular outcome is significantly impaired. Furthermore, these changes increase the need for surgical or endovascular interventions and impair their outcomes. This is potentially due to current cardioprotective techniques being insufficiently tailored to the specific needs of these patients. The following review discusses the observed cardiomyocyte changes and systemic factors contributing to these changes. It describes the ensuing problems in cardioprotection and discusses strategies that can be taken to divert or circumvent these detrimental changes.